The Influence of Current Ratio (CR) and Net Profit Margin (NPM) on Profit Growth at PT Japfa Comfeed Indonesia, Tbk (Periods 2013 – 2022) - Setiani, Suci N; Nufzatutsaniah, Nufzatutsaniah (Indonesian Development of Economics and Administration Journal, 2024)
This research aims to identify the influence of Current Ratio (CR) and Net Profit Margin (NPM) on Profit Growth at PT Japfa Comfeed Indonesia, Tbk. The method used in this research is a quantitative method. With data analysis involving classical assumption tests, correlation coefficient tests, coefficient of determination tests, multiple linear regression tests, and hypothesis tests. The results of the coefficient of determination test show an influence of 63,8% of the Current Ratio and Net Profit Margin on Profit Growth, the remaining 36,2% is influenced by other variables, then based on the t test the results show 0,015 < 1,895 with a significance of 0,003 < 0,05, meaning Current Ratio (CR) does not have a significant effect on Profit Growth, while the subsequent t test results show results of 1,95 > 1,895 with a significance of 0,001 < 0,05, meaning that Net Profit Margin (NPM) has a significant effect on Profit Growth. Based on the hypothesis test (f test), the results show 6,161 > 4,74 with a significance of 0,002< 0,05, meaning that simultaneously the Current Ratio (CR) and Net Profit Margin (NPM) have a significant effect on Profit Growth.